British Gynaecological Cancer Society recommendations and guidance on patient-initiated follow-up (PIFU). Issue 5 (19th April 2020) - Newton, Claire; Nordin, Andy; Rolland, Philip; Ind, Thomas; Larsen-Disney, Peter; Martin-Hirsch, Pierre; Beaver, Kinter; Bolton, Helen; Peevor, Richard; Fernandes, Andrea; Kew, Fiona; Sengupta, Partha; et al.
Abstract : The National Cancer Survivorship Initiative through the National Health Service (NHS) improvement in the UK started the implementation of stratified pathways of patient-initiated follow-up (PIFU) across various tumor types. Now the initiative is continued through the Living With and Beyond Cancer program by NHS England. Evidence from non-randomized studies and systematic reviews does not demonstrate a survival advantage to the long-established practice of hospital-based follow-up regimens, traditionally over 5 years. Evidence shows that patient needs are inadequately met under the traditional follow-up programs and there is therefore an urgent need to adapt pathways to the needs of patients. The assumption that hospital-based follow-up is able to detect cancer recurrences early and hence improve patient prognosis has not been validated. A recent survey demonstrates that follow-up practice across the UK varies widely, with telephone follow-up clinics, nurse-led clinics and PIFU becoming increasingly common. There are currently no completed randomized controlled trials in PIFU in gynecological malignancies, although there is a drive towards implementing PIFU. PIFU aims to individualize patient care, based on risk of recurrence and holistic needs, and optimizing resources. The British Gynaecological Cancer Society wishes to provide the gynecological oncology community with guidance and a recommendations statement regarding the value, indications, and limitations of PIFU in endometrial, cervical, ovarian, and vulvar cancers in an effort to standardize practice and improve patient care.